Interações entre estrutura da vegetação e fertilidade do solo na decomposição da matéria orgânica em diferentes usos do solo - Bessi, Débora (2021)
Forests play a fundamental role in providing ecosystem functions and services. In particular, the relationship between forest and soil is an important link for ecosystem functioning and maintenance of services such as nutrient cycling. Despite this, a high loss of natural forest area has been observed, mainly due to the conversion into agricultural area, strongly impacting the biogeochemical cycles. Agroforestry systems and ecological restoration practices are capable of playing a fundamental role in the resumption of ecosystem functions. It is expected that the introduction and growth of the plant community favors nutrient cycling and carbon fixation, which are strongly influenced by organic matter decomposition rates. The litter decomposition process is complex, involving interactions between physical, chemical and biological soil characteristics, litter chemical characteristics, local vegetation structure and climatic variation. Thus, this study aimed to evaluate the effects of plant structure and soil quality, in areas with different land uses, on the decomposition processes of organic matter as estimated by decomposition rates k and stabilization factor S. We used the TBI (Tea Bag Index) method to assess k and S and evaluate decomposition in agroforestry systems, successional stands at different ages of forest restoration and mature riparian forests. The direct and indirect effects of the sampled variables were estimated using structural equation models. Our results showed that intensive pasture systems and pastures intercropped with crops present a more dynamic nutrient cycling (higher k), whereas in areas with silviculture inclusion there was a greater contribution of recalcitrant organic matter and material stabilization (higher S). When comparing riparian forest areas, restored areas and pastures, the results indicated that the stabilization of organic material is greater in forest areas compared to pasture areas, with a tendency to increase with the advancement of succession and soil fertility. In contrast, decomposition rates were higher in open areas under pasture, but also showed a positive variation with nutrient content. These results suggest that the diversification of integration systems favors nutrient cycling and carbon sequestration due to the lower nutrient loss through decomposition and stabilization of the organic matter, contributing to the sustainable management of pastures. In addition, plant restoration practices can be a good strategy to increase the input of organic material into the soil considering the increase in organic matter stabilization when compared to pastures, contributing to the improvement of its quality and, mainly, increasing carbon sequestration via stabilized material.